Elevated HIV Prevalence Despite Lower Rates of Sexual Risk Behaviors Among Black Men in the District of Columbia Who Have Sex with Men - Magnus, Manya (AIDS Patient Care STDS, 2010)
The District of Columbia (DC) has among the highest HIV/AIDS rates in the United States, with 3.2% of the population and 7.1% of black men living with HIV/AIDS. The purpose of this study was to examine HIV risk behaviors in a community-based sample of men who have sex with men (MSM) in DC. Data were from the National HIV Behavioral Surveillance system. MSM who were 18 years were recruited via venue-based sampling between July 2008 and December 2008. Behavioral surveys and rapid oral HIV screening with OraQuick ADVANCE ½ (OraSure Technologies, Inc., Bethlehem, PA) with Western blot confirmation on positives were collected. Factors associated with HIV positivity and unprotected anal intercourse were identified. Of 500 MSM, 35.6% were black. Of all men, 14.1% were confirmed HIV positive; 41.8% of these were newly identified HIV positive. Black men (26.0%) were more likely to be HIV positive than white (7.9%) or Latino/Asian/other (6.5%) men (p < 0.001). Black men had fewer male sex partners than non-black, fewer had ever engaged in intentional unprotected anal sex, and more used condoms at last anal sex. Black men were less likely to have health insurance, have been tested for HIV, and disclose MSM status to health care providers. Despite significantly higher HIV/AIDS rates, black MSM in DC reported fewer sexual risks than non-black. These findings suggest that among black MSM, the primary risk of HIV infection results from nontraditional sexual risk factors, and may include barriers to disclosing MSM status and HIV testing. There remains a critical need for more information regarding reasons for elevated HIV among black MSM in order to inform prevention programming.